Removal of Flotation Collector O-Isopropyl-N-ethylthionocarbamate from Wastewater - Zhe Wang (MDPI AG, 2021)
Flotation collector O-isopropyl N-ethylthionocarbamate (IPETC) is widely used for separation of sulfide ores. Its removal from water by several oxidation processes was studied. Photocatalytic oxidation with air in the presence of iron salts, utilizing solar irradiation or artificial UV-A light is very efficient. Oxidation leads through the formation of O-isopropyl N-ethylcarbamate and several other reaction intermediates to total decomposition of organic compound in the final stage in 1 day. Similar results were obtained with a Fenton type oxidation with hydrogen peroxide and iron salts. Treatment with sodium hypochlorite yields mainly O-isopropyl N-ethylcarbamate. The formation of this compound in wastewaters can be of concern, since simple alkyl carbamates are cancer suspect agents.